Effects of ATRAP in Renal Proximal Tubules on Angiotensin‐Dependent Hypertension. Issue 8 (16th April 2019) - Kinguchi, Sho; Wakui, Hiromichi; Azushima, Kengo; Haruhara, Kotaro; Koguchi, Tomoyuki; Ohki, Kohji; Uneda, Kazushi; Matsuda, Miyuki; Haku, Sona; Yamaji, Takahiro; Yamada, Takayuki; Kobayashi, Ryu; et al.
Abstract : Background: We have previously shown that ATRAP (angiotensin II receptor–associated protein; Agtrap ) interacts with AT1R (angiotensin II type 1 receptor) and promotes constitutive internalization of AT1R so as to inhibit hyperactivation of its downstream signaling. In response to angiotensin II, systemic ATRAP deficiency exacerbates angiotensin II–mediated hypertension via hyperactivation of renal tubular AT1R. Although ATRAP expression is abundant in renal proximal tubules, little is known about the actual function of renal proximal tubule ATRAP in angiotensin‐mediated hypertension. Methods and Results: In this study, we examined the in vivo functional role of renal proximal tubule ATRAP in angiotensin‐dependent hypertension. We succeeded in generating proximal tubule–specific ATRAP knockout (PT‐KO) mice for the first time using the Cre/loxP system with Pepck ‐Cre. Detailed analysis of renal ATRAP expression in PT‐KO mice estimated by immunohistochemical and laser‐capture microdissection analysis revealed that ATRAP mRNA expression decreased by ≈80% in proximal regions of the nephron in PT‐KO mice compared with wild‐type (WT) mice. We compared blood pressure of PT‐KO and WT mice using both tail‐cuff and radiotelemetric methods. Blood pressure of PT‐KO mice was comparable with that of WT mice at baseline. Moreover, no significant differences were noted in pressor response to angiotensin II (600 ng/kg per min or 1000 ng/kg per minute) infusion between PT‐KO and WT mice. In addition, angiotensin II–mediated cardiac hypertrophy was identical between PT‐KO and WT mice. Conclusions: ATRAP deficiency in proximal tubules did not exacerbate angiotensin‐dependent hypertension in vivo. The results indicate that renal proximal tubule ATRAP has a minor role in angiotensin‐dependent hypertension in vivo.